1989
DOI: 10.1007/bf01540042
|View full text |Cite
|
Sign up to set email alerts
|

Motility changes in opossum esophagus from experimental esophagitis

Abstract: We assessed how acute inflammation affects the contractile activity of the esophageal body. Two models of esophagitis were used: nine opossums had an esophageal perfusion of 100 meq hydrochloric acid for 2 hr and were studied at 24 hr. Ten had the perfusion for 4 h and their esophagitis were studied in vitro after 72 hr. Comparisons were made in all instances to animals who had esophageal saline perfusion for identical periods. All acid-perfused animals developed gross and histologic evidence of mucosal inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 18 publications
2
26
0
1
Order By: Relevance
“…In agreement with previous studies, we found that acute esophagitis significantly reduced the frequency and amplitude of peristaltic contractions in the esophagus (7,16,24). Previous animal studies used acute experiments and did not follow up on the spontaneous evolution of motility changes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with previous studies, we found that acute esophagitis significantly reduced the frequency and amplitude of peristaltic contractions in the esophagus (7,16,24). Previous animal studies used acute experiments and did not follow up on the spontaneous evolution of motility changes.…”
Section: Discussionsupporting
confidence: 92%
“…Previous animal studies with acute experimental esophagitis demonstrated an increased intraesophageal baseline pressure (16) or a high baseline tension in muscle strips from the esophageal body (24). To the best of our knowledge, this is the first description of esophageal tone changes, measured with a barostat, during acute esophagitis.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In the previous study, LES pressure, the success rate, and the amplitude of primary peristalsis in patients with RE increased after treatment, compared with before treatment [15]. In some animal experiments, it has been reported that LES pressure or the amplitude of peristalsis decreased after experimental esophagitis [16,17,18]. These results are consistent with our results; however, there is a contrary view.…”
Section: Discussionsupporting
confidence: 64%
“…However, we did not find any gender-related differences. Such hyperreactivity was also seen in animal studies (40). Acid perfusion may result in sensitization of mucosal afferents as well as central hyperexcitability (23,41).…”
Section: Gender Differences To Mechanical and Thermal Stimulation Befmentioning
confidence: 90%